Mechano-redox control of integrin de-adhesion - Passam, Freda; Kolšek, Katra; Thärichen, Lena; Aponte-Santamaria, Camilo; Gräter, Frauke (eLife, 2018)
How proteins harness mechanical force to control function is a significant biological question. Here we describe a human cell surface receptor that couples ligand binding and force to trigger a chemical event which controls the adhesive properties of the receptor. Our studies of the secreted platelet oxidoreductase, ERp5, have revealed that it mediates release of fibrinogen from activated platelet αIIbβ3 integrin. Protein chemical studies show that ligand binding to extended αIIbβ3 integrin renders the βI-domain Cys177-Cys184 disulfide bond cleavable by ERp5. Fluid shear and force spectroscopy assays indicate that disulfide cleavage is enhanced by mechanical force. Cell adhesion assays and molecular dynamics simulations demonstrate that cleavage of the disulfide induces long-range allosteric effects within the βI-domain, mainly affecting the metal-binding sites, that results in release of fibrinogen. This coupling of ligand binding, force and redox events to control cell adhesion may be employed to regulate other protein-protein interactions.
Gesehen am 04.08.2020